Comparative Analysis of the Pathogen Structure in Patients with Community-Acquired and Nosocomial Pneumonia in Medical Organizations of the Rostov, Tyumen Regions and Khabarovsk Territory at the Current Stage of a New Coronavirus Infection Pandemic - N. V. Pavlovich; O. S. Chemisova; N. V. Aronova; M. V. Tsimbalistova; A. S. Anisimova; E. N. Gudueva; O. N. Kolotova; L. V. Kataeva; K. B. Stepanova; A. P. Bondarenko; E. D. Teplyakova; O. E. Trotsenko; et al. (Проблемы особо опасных инфекций, 2023)
The aim of the study was to conduct a comparative analysis of the spectrum and antibiotic resistance of secondary pneumonia pathogens isolated in the territories of the Rostov, Tyumen Regions and Khabarovsk Territory against the background of a new coronavirus infection pandemic.Materials and methods. We investigated sputum samples from coronavirus-positive and coronavirus-negative patients with community-acquired pneumonia from medical organizations using bacteriological method, PCR mass spectrometry.Results and discussion. The study of the etiological structure of secondary pneumonia agents isolated from patients in medical organizations of the Southern, Ural and Far Eastern Federal Districts has revealed that the dominant cultures in SARS‑CoV‑2 “+” and SARS‑CoV‑2 “–” patients were yeast and yeast-like fungi. It has been found that under diversity of isolated fungi, Candida albicans species prevailed. The bacterial microflora is represented by a variety of gram-positive and gram-negative bacteria, of which Staphylococcus aureus and Klebsiella pneumoniaе were most often present in sputum. It has also been established that even before hospitalization of patients, community-acquired pneumonia could be caused by microorganisms of the ESKAPE group (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniaе, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp.), which are usually considered as polyantibiotic-resistant pathogens of nosocomial infections. Moreover, in coronavirus-positive patients with secondary community-acquired pneumonia, those pathogens were isolated 2–3 times more frequently than in coronavirus-negative ones. Assessment of sensitivity/resistance of isolated strains to antibacterial drugs has revealed a general trend: the majority of the strains, regardless of the type, were characterized by a narrow spectrum of sensitivity, having 3 or more markers of antibiotic resistance. This confirms the necessity and expediency of microbiological support of the patient during the entire infectious process. The most adequate drugs of choice, providing activity against 60–70 % of strains of the Enterobacteriaceae family, are amikacin and cefoperazone/sulbactam.